Competitiveness in the World of E-Commerce: The Influence of Price and Service on Consumer Purchase Interest at Babyshop - Yuaniko, Yuaniko; Sejati, Khoirunnisa (Research of Business and Management, 2025)
This study analyzes the influence of price and service quality on consumer purchase intention at Permai Babyshop, Jakarta Timur, through the Shopee marketplace. The research is driven by the growing competition in online retail and the importance of pricing strategies and service quality in shaping consumer behavior. Permai Babyshop, which shifted from traditional retail to e-commerce after the COVID-19 pandemic, provides a relevant case. Using a quantitative approach, data were collected from 100 Shopee customers through questionnaires. Multiple linear regression was employed to examine the effects of price and service quality (independent variables) on purchase intention (dependent variable). Results show that both variables have a positive and significant influence. Affordable and competitive prices, along with responsive, reliable, and empathetic service, increase consumer interest and loyalty. The findings highlight that online retailers must continuously improve pricing strategies and service quality to meet expectations in the digital marketplace. For Permai Babyshop, aligning price with perceived value and ensuring service excellence are critical to fostering engagement and sustainable growth. This study contributes to managerial practice by emphasizing customer-focused strategies that enhance purchase intention and strengthen competitiveness in online retail.